2019
DOI: 10.18820/2519593x/pie.v37i2.6
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Analysis of Virtual and Traditional Laboratory Chemistry Learning.

Abstract: Laboratory experimentation in the context of school science is a widely advocated teaching strategy for the simplification of several abstract scientific concepts. Laboratory-based learning activities have proven to enhance learners' conceptual and procedural understandings of micro chemical phenomena, thus boosting achievement in chemistry content tests. In the South African education landscape where there is inequitable distribution of resources for laboratory-based science learning, this study exploited how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…In summary, the data suggest that using VR and BanAnatomy resulted in equal knowledge acquisition and retention of anatomical spatial relationships. These findings are further supported by previous studies showing equivalent student outcomes between in-person and online laboratory modules in other subjects [ 53 55 ]. Worth mentioning, VR students outperformed 2D students later in the semester, suggesting that level and duration of program usage play a role in student retention using VR as a tool to study human anatomy.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In summary, the data suggest that using VR and BanAnatomy resulted in equal knowledge acquisition and retention of anatomical spatial relationships. These findings are further supported by previous studies showing equivalent student outcomes between in-person and online laboratory modules in other subjects [ 53 55 ]. Worth mentioning, VR students outperformed 2D students later in the semester, suggesting that level and duration of program usage play a role in student retention using VR as a tool to study human anatomy.…”
Section: Discussionsupporting
confidence: 88%
“…Several studies have shown that if online STEM modules are intentionally designed and integrated, online students perform equally well compared to F2F instruction [ 36 , 53 55 ]. Though limited, previous studies utilizing VR in human anatomy and neuroanatomy have reported similar findings; students learning in VR demonstrate similar outcomes compared with F2F instruction [ 44 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is despite the overwhelming literature reporting that face-to-face and alternative modes of delivery are essentially equivalent. [24][25][26][27][28][29][30][31][32] Over the years, many strategies have been developed and explored for practical work in the sciences that support online and distance learning. They can be grouped into five teaching laboratory types that can potentially be considered by the science educator for inclusion in their course (Fig.…”
Section: Science Laboratories At a Distancementioning
confidence: 99%
“…The material being experimented on was material that did not require various tools and materials. Activities in the laboratory are proven to positively impact student learning outcomes because abstract material can be experimented with [2].…”
Section: Chemistry Learningmentioning
confidence: 99%
“…Understanding chemistry depends on understanding abstract things, so it is not easy to connect various chemical concepts [1]. Abstract material can be studied by conducting experiments or practicum in the laboratory because it is proven that learning in the laboratory positively impacts students' chemistry learning outcomes [2]. Practicum activities in the laboratory make a positive contribution to achieving learning goals [3].…”
Section: Introductionmentioning
confidence: 99%